In Vitro Toxicity Evaluation of Engineered Cadmium-Coated Silica Nanoparticles on Human Pulmonary Cells - Uliana De Simone; Luigi Manzo; Antonella Profumo; Teresa Coccini (Journal of Toxicology)
Cytotoxicity of cadmium-containing silica nanoparticles Cd-SiO2NPs (0.05–100 µg/mL) versus SiO2NPs and CdCl2 was evaluated by an in vitro test battery in A549 by assessing (i) mitochondrial function, (ii) membrane integrity/cell morphology, (iii) cell growth/proliferation, (iv) apoptotic pathway, (v) oxidative stress, after short- (24–48 h) and long-term (10 days) exposure. Both Cd-SiO2NPs and CdCl2 produced dose-dependent cytotoxic effects: (i) MTT-assay: similar cytotoxicity pattern was observed at both 24 and 48 h, with a more Cd-SiO2NPs pronounced effect than CdCl2. Cd-SiO2NPs induced mortality (about 50%) at 1 μg/mL, CdCl2 at 25 μg/mL; (ii) calcein-AM/PI staining: decrease in cell viability, noticeable at 25 μg/mL, enhanced markedly at 50 and 100 μg/mL, after 24 h. Cd-SiO2NPs induced higher mortality than CdCl2 (25% versus 4%, resp., at 25 μg/mL) with further exacerbation after 48h; (iii) clonogenic assay: exposure for longer period (10 days) compromised the A549 proliferative capacity at very low dose (0.05 μg/mL); (iv) a progressive activation of caspase-3 immunolabelling was detected already at 1 μg/mL; (v) GSH intracellular level was modified by all compounds. In summary, in vitro data demonstrated that both Cd-SiO2NPs and CdCl2 affected all investigated endpoints, more markedly after Cd-SiO2NPs, while SiO2NPs influenced GSH only.